Hospitalization by cytotoxic chemotherapy regimen among older women with stage IV breast cancer. Issue 24 (28th September 2018) - Kehl, Kenneth L.; Niu, Jiangong; Chavez‐MacGregor, Mariana; Giordano, Sharon H.
Abstract : Background: Older patients with cancer are at risk for increased side effects of treatment. Our goal was to inform treatment for older patients by analyzing the relationship between chemotherapy regimen and hospitalization among older women receiving palliative cytotoxic chemotherapy for breast cancer. Method: We identified women aged 66‐99 years with stage IV de novo breast cancer diagnosed between 2010 and 2013 who received any of the 10 most common cytotoxic chemotherapy‐containing regimens in the Surveillance, Epidemiology, and End Results (SEER)‐Medicare database. The primary outcome was hospitalization or death within 30 days of starting a new line of chemotherapy. Generalized linear mixed effects models with patient‐specific random effects were used for multivariable analysis of the association between chemotherapy regimen and this outcome. Additional covariates included number of prior lines of therapy; time since diagnosis; hormone receptor and HER2 status; sites of metastatic disease; and age, race, and marital status. The unit of analysis was each new line of chemotherapy. Results: Of 972 lines of chemotherapy initiated among 693 patients, 188 (19%) were followed by hospitalization or death within 30 days. After adjustment, there was significant variation in this outcome by chemotherapy regimen ( P = .03); compared with capecitabine, hospitalization/death rates were higher with cyclophosphamide + docetaxel (odds ratio [OR], 2.71; 95% confidence interval [CI], 1.31‐5.59), cyclophosphamide + doxorubicin (OR, 2.45; 95% CI, 1.19‐5.03), docetaxel (OR, 2.49; 95% CI, 1.19‐5.21), and gemcitabine (OR, 3.51; 95% CI, 1.72‐7.19). Conclusion: Treatment regimen was associated with significant variation in 30‐day hospitalization or death among older women receiving cytotoxic chemotherapy for stage IV de novo breast cancer. Abstract : Palliative‐intent chemotherapy is associated with substantial near‐term hospitalization risks among elderly patients with stage IV breast cancer. These risks may vary according to chemotherapy regimen.